Clinical Implications for Exercise at Altitude Among Individuals With Cardiovascular Disease<subtitle>A Scientific Statement From the American Heart Association</subtitle> - William K. Cornwell; Aaron L. Baggish; Yadav Kumar Deo Bhatta; Maria Joan Brosnan; Christoph Dehnert; J. Sawalla Guseh; Debra Hammer; Benjamin D. Levine; Gianfranco Parati; Eugene E. Wolfel (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2021)
An increasing number of individuals travel to mountainous environments for work and pleasure. However, oxygen availability declines at altitude, and hypoxic environments place unique stressors on the cardiovascular system. These stressors may be exacerbated by exercise at altitude, because exercise increases oxygen demand in an environment that is already relatively oxygen deplete compared with sea‐level conditions. Furthermore, the prevalence of cardiovascular disease, as well as diseases such as hypertension, heart failure, and lung disease, is high among individuals living in the United States. As such, patients who are at risk of or who have established cardiovascular disease may be at an increased risk of adverse events when sojourning to these mountainous locations. However, these risks may be minimized by appropriate pretravel assessments and planning through shared decision‐making between patients and their managing clinicians. This American Heart Association scientific statement provides a concise, yet comprehensive overview of the physiologic responses to exercise in hypoxic locations, as well as important considerations for minimizing the risk of adverse cardiovascular events during mountainous excursions.